Development of Scaled Damage Criteria for Blasting - Jorge Alvarez (International Society of Explosives Engineers, 2025)
In a large-scale open-pit mining operation, continuous efforts are made to control damage to the slope walls. An essential tool in this effort is determining the PPVc (critical peak particle velocity) in areas of interest. By knowing this value and generating criteria, drilling and blasting designs can be established to reduce vibrations that affect wall construction. It is crucial to understand that the PPVc changes as different mining phases develop, especially due to exploitation on the benches, which leads to vertical inherited damage. Therefore, it is imperative to regularly update the PPVc based on field tests that provide accurate data. With this information, vibration damage criteria can be established, and drilling and blasting techniques can be designed to minimize the impact on the remaining rock mass. This document presents a methodology for generating scaled criteria that best represent the reality of the rock mass.